Perception of Medical Students regarding “Swachh Bharat Abhiyan” a cleanliness campaign: a qualitative study - Nath, Bhola; Yadav, Shiv Kumar; Kumari, Ranjeeta (Indian Journal of Community Health, 2018)
Background: Swachh Bharat Abhiyan -A Cleanliness Campaign was launched all over India in 2014 to sensitize people to work in the direction of making India a clean country. Since youth constitute the future of the nation, their perception is very much important for the nation’s progress. Therefore, the present study was conducted among Indian medical undergraduate (IMUG) students regarding their perception about the current cleanliness drive going on in the country. Aims & Objective: To assess the perception of IMUG students about the cleanliness and innovative cleanliness practices. Study Setting & Design: A cross-sectional qualitative study was carried among IMUG students in a medical college of North India. Material & Methods: Study was conducted during the period of the Swachhata Pakhwara Abhiyan, celebrated all over the country to reinforce the cleanliness drive. IMUG students were invited to describe their perception on the topic “How can I keep My India clean”. Statistical Analysis: -Transcript was prepared and deductive coding was done and perceptions of students were categorized into four broad themes: -1. Behaviour change communication 2. Practicing cleanliness.3Interventions required for cleanliness 4. Legislation required in favour of cleanliness. Results: Majority of IMUG Students expressed that it is the behaviour change Communication and habit of practicing cleanliness everywhere, which will bring the change in cleanliness drive in the country with emphasis on innovative intervention and the role of legislation. Conclusion: -Proper direction and consistent motivation along with sound perception of cleanliness among citizens can contribute in reaching the desired goals of cleanliness.